Experimental investigation on the effect of working fluid charge in a −120 °C turbo-refrigerator - Shujian Song; Xiufang Liu; Ze Zhang; Zhefeng Wang; Shuangtao Chen; Yu Hou (Case Studies in Thermal Engineering)
Most existing studies overlooked the impact of the working fluid charge on turbo-refrigerators for ultralow-temperature applications, especially not on the motor-driven turboexpander-compressor (MTEC) based turbo-refrigerators. This study addresses this gap by conducting an experimental study on a newly developed MTEC-based turbo-refrigerator prototype for ultralow-temperature freezing down to −120 °C. The prototype was tested at charge pressures ranging from 249.3 to 438.1 kPa and at different heat loads and at a maintained input power level. Test results indicate the effect of charge pressure on both compressor and expander efficiencies are negligible, whereas both the MTEC's additional efficiency and recuperator effectiveness exhibit a significant increase with increasing charge pressure. The increase in the recuperator effectiveness mitigates the decline in relative Carnot efficiency accounting for no additional losses with increasing charge pressure. Combined with the increased additional efficiency, this results in the net relative Carnot efficiency being only slightly affected by changes in charge pressure. Nevertheless, a slight peak net Carnot efficiency of 9.8 % corresponding to a test charge pressure of 294.6 kPa was noted for the presented prototype. When heat load levels are considered together, changing charge pressure has a greater effect on the relative Carnot efficiency at lower heat loads.